2023
DOI: 10.2147/oarrr.s403403
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Performance of Anti-Topoisomerase-I, Anti-Th/To Antibody and Anti-Fibrillarin Using Immunoblot Method in Systemic Sclerosis Related Interstitial Lung Disease Patients

Abstract: Purpose Systemic Sclerosis related Interstitial Lung Disease (SSc-ILD) is the most common clinical manifestation of SSc with a high morbidity and mortality rate. However, the Thorax High-Resolution Computed Tomography (HCRT) as the gold standard diagnostic tool for SSc-ILD is not widely equipped in health-care facilities. Recently, specific autoantibody examination (anti-topoisomerase-1 (ATA), anti-Th/To antibody, and anti-fibrillarin) has been studied and used for SSc-ILD diagnosis. This study ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
(29 reference statements)
0
0
0
Order By: Relevance
“…Comparing anti-Th/To patients with lcSSc to those that are ACA-positive, the first group has more subtle cutaneous and vascular involvement [ 39 ] and a mild clinical manifestation of the disease [ 40 ]. However, recent reports seem to deny the predisposition of anti-Th/To-positive patients to a mild course of the disease [ 36 , 39 , 41 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 3 more Smart Citations
“…Comparing anti-Th/To patients with lcSSc to those that are ACA-positive, the first group has more subtle cutaneous and vascular involvement [ 39 ] and a mild clinical manifestation of the disease [ 40 ]. However, recent reports seem to deny the predisposition of anti-Th/To-positive patients to a mild course of the disease [ 36 , 39 , 41 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
“…The profile of SSc-ILD varies widely, with less than a quarter of patients developing progressive fibrosing ILD, leading to respiratory insufficiency [ 44 , 45 ]. Due to their high specificity, anti-Th/To antibodies can serve as a reliable diagnostic marker for SSc-ILD [ 41 ]. While Mitri’s study showed that ILD is more common among Th/To patients compared to ACA-positive patients (48% vs. 13%), Moschetti et al showed that anti-Th/To-positive patients developed ILD less frequently (40% vs. 85%) and required less immunosuppression (8% vs. 41%) than anti-topo I-positive patients [ 40 ].…”
Section: Clinical Featuresmentioning
confidence: 99%
See 2 more Smart Citations